Analisis Komunikasi, Kedisiplinan, Beban Kerja Dan Semangat Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pengendalian Penduduk Dan Keluarga Berencana (DPPKB) Kabupaten Labuhanbatu Utara - Lubis, Sri Mawarni (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of communication, discipline, workload and morale on the performance of employees at the Office of Population Control and Family Planning (Dppkb) North Labuhanbatu Regency. The sample in this research 39 respondents using SPSS 22.0. The results showed that communication, discipline, workload and morale affect partially and simultaneously the performance of employees at the Office of Population Control and Family Planning (Dppkb) North Labuhanbatu Regency. From the results of data processing in the t test (partial) the value of the count for the communication variable (1.777) with a significant value of 0.001, discipline of (3.964) with a significant value of 0.000, workload of (1.183) with a significant value of 0.019, morale of (6.693) with a significant value of 0.000, while the value of ttable is sought in the T table with the level of test a = 5% and df (n-k-1) = (39-5-1) = 33 so that the value of ttable obtained by 1692. Thus the hypothesis is accepted. From the results of data processing in the test F (simultaneous) DF obtained by Count (k-1) = (5-1) = 4 while Df2 obtained calculation (N-k) = (39-5-1) = 33 with a = 5% so the value Ftable = 2.66 value F count > F table = 45.837 > 2.66 with a significant value of 0.000 < 0.05 thus simultaneously communication, discipline, workload and morale have a significant influence on North labuhanbatu. Thus the hypothesis is accepted.